Analysis of individual cathecin from green tea extracted and fractionated by column chromatography - Rohdiana, Dadan; Shabri, Shabri (Research Institute for Tea and Cinchona, 2012)
A study determination of solvent and eluent on extraction process and fractination of individual cathecin especially epigallocathecin gallate (EGCG) by column chromatography method. This study devided on two steps, i.e. determination of raw material, solvent, process optimation for extraction and fravtination of green tea extract, evaporation and drying. Characterization of polyphenol conducted by visible spectrophotometer, analysis of individual cathecin by HPLC. This study was did in Laboratory of Processing Technology and Laboratory of Testing for Tea and Cinchona, Research Institute for Tea and Cinchona, at September 2007 up to March 2008. Result of this study shown that ratio of solvent aceton and water 7:3 v/v, ratio of tea and solvent 1:15 w/v for 15 minutes at 55-60ºC obtained 53.39% polyphenol on extract and yield gradiently produce extract with purity of cathecin is 94% b/b, EGCG 64.03% from feed with cathecin content is 82.96% w/w and EGCG 42.34% w/w.